SADI 2025 Congress: Scientific Report (Actualizaciones en Sida e Infectología, 2025)
The 25th Congress of the Argentine Society of Infectious Diseases (SADI) was held in Mar del Plata from June 12 to 14, 2025. SADI is the most important scientific event in the field in Argentina and one of the leading infectious disease meetings in Latin America. This edition had more than 3,900 registered participants and offered 135 hours of scientific activities, distributed among keynote lectures, roundtables, symposia, workshops, intersociety conferences, and clinical case discussions.
Keywords: 25th Congress of the Argentine Society of Infectious Diseases (SADI); report